Mid-Infrared Polarization Spectroscopy Measurements of Species Concentrations and Temperature in a Low-Pressure Flame. Issue 6 (June 2019) - Sahlberg, Anna-Lena; Hot, Dina; Lyngbye-Pedersen, Rasmus; Zhou, Jianfeng; Aldén, Marcus; Li, Zhongshan
We demonstrate quantitative measurements of methane (CH4 ) mole fractions in a low-pressure fuel-rich premixed dimethyl ether/oxygen/argon flat flame (Φ = 1.87, 37 mbar) using mid-infrared (IR) polarization spectroscopy (IRPS). Non-intrusive in situ detection of CH4, acetylene (C2 H2 ), and ethane (C2 H6 ) in the flame was realized by probing the fundamental asymmetric C–H stretching vibration bands in the respective molecules in the spectral range 2970–3340 cm −1 . The flame was stabilized on a McKenna-type porous plug burner hosted in a low-pressure chamber. The temperature at different heights above the burner (HAB) was measured from the line ratio of temperature-sensitive H2 O spectral lines recorded using IRPS. Quantitative measurements of CH4 mole fractions at different HAB in the flame were realized by a calibration measurement in a low-pressure gas flow of N2 with a small admixture of known amount of CH4 . A comprehensive study of the collision effects on the IRPS signal was performed in order to quantify the flame measurement. The concentration and temperature measurements were found to agree reasonably well with simulations using Chemkin. These measurements prove the potential of IRPS as a sensitive, non-intrusive, in situ technique in low pressure flames.